Inhibitory control development from infancy: identifying neural correlates and mapping behavioural trajectories into early childhood - Fiske, A (2023)
This thesis aims to investigate the behavioural development and neural correlates of inhibitory control across two key transitions in the early years of life. To do so, four experimental chapters are presented that report data from a longitudinal sample of participants at three age points: infancy (10-months), the transition to toddlerhood (16-months), and the start of early childhood (3½ years). A literature review is provided in the general introduction (Chapter 1), the methodological approaches taken to measure early inhibitory control development are described in Chapter 2, and an introduction to functional near-infrared spectroscopy (fNIRS) is presented in Chapter 3. The first three experimental chapters (Chapters 4 – 6) used fNIRS alongside an age-appropriate task to investigate the behavioural development and neural correlates of response inhibition across the first four years of life. Whilst there was no response inhibition improvement from 10- to 16-months, there was substantial change in the brain regions that were more active when inhibition was required at 16-months. By early childhood, response inhibition performance had significantly improved, yet there was some commonality in the brain regions recruited when inhibition was required at both 16-months and 3½ years. Chapter 7 presents a longitudinal examination of the development of ‘hot’ and ‘cool’ inhibitory control and investigates predictive associations with pre-academic skills in early childhood. Whilst there was some consistency in inhibitory control performance between tasks in infancy and early childhood, there was no evidence of longitudinal stability across development. Significant associations were found between ‘hot’ inhibitory control and early academic skills at 3½ years, suggesting that early inhibitory control skills may have an important role in early numeracy and language skills in the preschool years. Finally, Chapter 8 includes a discussion of the contributions this thesis makes to the field and evaluates the strengths and limitations of this research.